Factors associated with employment discontinuation among older and working age survivors of oropharyngeal cancer. Issue 11 (6th September 2019) - Check, Devon K.; Hutcheson, Katherine A.; Poisson, Laila M.; Pocobelli, Gaia; Sakoda, Lori C.; Zaveri, Jhankruti; Chang, Steven S.; Chubak, Jessica
Abstract: Background: Oropharyngeal cancer survivors experience difficulty returning to work after treatment. To better understand specific barriers to returning to work, we investigated factors associated with discontinuing employment among older and working‐age survivors. Methods: The sample included 675 oropharyngeal cancer survivors (median: 6 years posttreatment) diagnosed from 2000 to 2013 and employed at diagnosis. Relative risk models were constructed to examine the independent associations of demographic and health factors, and symptom experiences per the MD Anderson Symptom Inventory ‐ Head and Neck Module (MDASI‐HN) with posttreatment employment, overall and by age (<60 years vs ≥60 years at survey). Results: Symptom interference was not statistically significantly associated with posttreatment employment status among respondents ≥60 years. Among working‐age respondents <60 years, symptom interference was strongly associated with posttreatment employment. Conclusions: Efforts to assess and lessen symptom burden in working‐age survivors should be evaluated as approaches to support regaining core functions needed for continued employment.